2022
DOI: 10.1021/acs.jmedchem.2c01599
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Inhibitors of Protein Kinase D: Early Development, Current Approaches, and Future Directions

Abstract: Now entering its fourth decade, research on the biological function, small molecule inhibition, and disease relevance of the three known isoforms of protein kinase D, PKD1, PKD2, and PKD3, has entered a mature development stage. This miniperspective focuses on the medicinal chemistry that provided a structurally diverse set of mainly active site inhibitors, which, for a brief time period, moved through preclinical development stages but have yet to be tested in clinical trials. In particular, between 2006 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…In this in vitro panel assay, 12b showed strong interaction with PKD2, HPK1, and AurB and has an excellent selectivity profile over other kinases. Interestingly, PKD2, HPK1, and AurB are considered as promising targets for tumor immunotherapy. This finding indicated that 12b has the potential to be a multitargeted receptor lead compound.…”
Section: Resultsmentioning
confidence: 99%
“…In this in vitro panel assay, 12b showed strong interaction with PKD2, HPK1, and AurB and has an excellent selectivity profile over other kinases. Interestingly, PKD2, HPK1, and AurB are considered as promising targets for tumor immunotherapy. This finding indicated that 12b has the potential to be a multitargeted receptor lead compound.…”
Section: Resultsmentioning
confidence: 99%